Integrating Material Recovery Facilities and RDF Technology for Waste Optimization in Small Cities: a Material Flow Analysis - Nando Ade Amarylly Putra; Arseto Yekti Bagastyo (Journal of Applied Geospatial Information, 2026)
The challenge of significantly increasing waste generation is not exclusive to metropolitan areas but is also faced by small cities, including Biak Numfor Regency, particularly within the population centers of Biak Kota and Samofa Districts. This study employs Material Flow Analysis (MFA) to map waste flows and evaluate technological interventions based on primary sampling data referring to SNI 3964:2025. The analysis reveals a waste composition dominated by organics (41.25%) and plastics (26.18%). Simulation results indicate that Scenario II, deploying six units of Material Recovery Facilities (TPS 3R), effectively meets National Medium-Term Development Plan of the Republic of Indonesia (RPJMN) 2029. Furthermore, Scenario III, which integrates TPS 3R with a Refuse Derived Fuel (RDF)-based Integrated Waste Processing Site (TPST), successfully suppresses landfill residue to below 10%, aligning with the National Long-Term Development Plan of the Republic of Indonesia (RPJPN) 2045. It is concluded that the proposed integrated infrastructure is technically feasible for achieving national reduction mandates. However, practical implementation requires fundamental operational reforms, specifically rigorous source segregation and modernized collection logistics to maintain feedstock quality and facility performance.